On Sense and Deform: Molecular Luminescence for Mechanoscience - Hirai, Yuichi (ACS applied optical materials, 2024)
Mechanoscientific research fields encompassing chemistry, physics, and biology have advanced significantly over the last two decades. Notably, the study of photon-emitting phenomena in molecular solids responsive to mechanical stimulation is known as mechanoresponsive luminescence (MRL) and mechanoluminescence (ML). These phenomena exhibit significant potential for applications such as sensor technology and anti-counterfeiting measures. The versatility observed in molecular designs, enabling control over responsive thresholds and wavelengths, coupled with diverse mechanisms for inducing deformation, such as heat, light, and sound, significantly broadens the domain of mechanically sensitive molecular materials. However, the understanding of the nanomechanical aspects about these molecular solids remains elusive. A comprehensive examination of the interplay among molecular structures, deformation characteristics, and luminescence responses is essential for further exploration. Such insights are crucial for addressing the intrinsic limitation of “one-time use” associated with deformation-induced properties, necessitating a focus on solid-state healing processes as well. Recent investigations into inorganic-based ML systems applied to free-standing light sources and mechanical metamaterial design foreshadow the future trajectory of molecular-based systems. These advancements aim to facilitate the secondary use of generated photons and the efficient capture/transfer of mechanical cues, enhancing optical output. Molecular luminescence stands poised to make substantial contributions to the ongoing rapid progress in mechanoscience due to an expanding synthetic repertoire, heightened biocompatibility, and precise “structural control” at molecular and macroscopic scales.